Connecting Elderly and Digital Devices: a Literature Review of User Interface Studies for Indonesian Elders - Ketut Ajeng Sespiani; Niken Febrina Ernungtyas (The Journal of Society and Media, 2022)
The impact of rapid change in technology infrastructure expedites our global economy. Today, most people in the big cities are inseparable from digital technology. Meanwhile, those who are unable to adapt are at real disadvantages. With the surging population growth of an aging society, these disadvantaged people are mainly elderly. Widespread dependency can become a catastrophic problem if not addressed immediately. Therefore, developing user interface (UI) designs specifically tailored to the needs and capabilities of elderly users are crucial. By using a descriptive qualitative approach by collecting various previous studies, the result of this paper suggesting that colourful interface, minimum icon usage, grid menu and bigger font size are the features that able to help the elders to operate digital devices. Moreover, the government’s role is needed to enhance the willingness and confidence of older adults by setting up the pieces trainings of digital devices throughout regions especially in rural areas.